2013
DOI: 10.1016/j.ijdevneu.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal undernutrition stimulates seeking food reward

Abstract: Experiments in animals have revealed that perinatal nutritional restriction, which manifests in adulthood, increases food intake and preference for palatable foods. Considering this, we aimed to evaluate the effects of perinatal malnutrition on hedonic control of feeding behavior. In this study, we divided Wistar rats into two groups according to the diet provided to their mothers during pregnancy and lactation: the control group (diet with 17% casein) and low-protein group (diet with 8% casein). We assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 58 publications
(81 reference statements)
6
27
0
Order By: Relevance
“…This study shows that animals that were subjected to protein perinatal malnutrition showed a body weight reduction in relation to control animals. These data are consistent with those of other studies (Remmers et al, 2008;Orozco-Solis et al, 2009;da Silva et al, 2013). The most frequent cause of body variation in weight in the early periods of life is the maternal nutritional contribution during the gestation and lactation periods (Page et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This study shows that animals that were subjected to protein perinatal malnutrition showed a body weight reduction in relation to control animals. These data are consistent with those of other studies (Remmers et al, 2008;Orozco-Solis et al, 2009;da Silva et al, 2013). The most frequent cause of body variation in weight in the early periods of life is the maternal nutritional contribution during the gestation and lactation periods (Page et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…At 70 days of age, rats in both the control and undernourished groups underwent a runway task incentive test (Silveira et al, 2010;da Silva et al, 2013). This test assesses the motivation of the animals Table 1 Composition of macronutrients of the diet and period handling.…”
Section: Runway Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…This model may be more reflective of poor quality maternal diets occurring in developing countries rather than IUGR in developed countries, where placental dysfunction is the major cause of IUGR (47). Exposure to a low protein diet throughout perinatal life appears to induce mild and variable effects on fetal growth, with none or 20% decrease in birth weight reported in various studies, and does not reduce litter size (3,20,30,64,65). Glucose homeostasis is impaired in progeny, at least in adult males, which have mildly elevated fasting glucose and impaired glucose tolerance (Supplementary Table S1).…”
Section: Models Of Iugr In Animalsmentioning
confidence: 99%
“…Severe maternal global nutrient restriction throughout pregnancy is followed by catch-up growth in some, but not all studies (84,130,141,144), and these progeny also exhibit increased adiposity (130,141,144), possibly due to increased appetite (75, 140 -142, 144). Maternal dietary protein restriction throughout gestation and lactation reduces body weight of male progeny into adulthood (3,20,25,26,30), but there is some evidence of altered hypothalamic control and increased appetite (20), so these animals may become fat if studied into later life. Prevention of neonatal catch-up growth may protect against increased visceral fatness after IUGR, as extending moderate maternal global nutrient restriction from late pregnancy throughout lactation results in progeny that not only remain smaller as adults (21,70,129) but are leaner than control animals and resistant to developing obesity when fed a high-fat diet (21,37,129).…”
Section: Insulin Secretionmentioning
confidence: 99%